2021
DOI: 10.3390/ijerph18041426
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Economic Impact of Reducing Loneliness in Community Dwelling Older People in England

Abstract: Loneliness has been associated with poor mental health and wellbeing. In England, a 2018 national strategy on loneliness was published, and public health guidelines recommend participation in social activities. In the absence of existing economic evidence, we modelled the potential cost effectiveness of a service that connects lonely older people to social activities against no-intervention. A 5-year Markov model was constructed from a health and social care perspective. Parameters were drawn from the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Engagement in diverse social activities in later life has been reported to provide opportunities for older adults to exchange similar interests, share life experiences, and facilitate social connections, which may alleviate their loneliness [ 40 , 41 ]. Our findings support previous literature reporting the beneficial effect of social activity on late-life loneliness in both men and women [ 15 , 41 ]. Being married was associated with a lower likelihood of loneliness, but only among men, which is consistent with a Japanese study that showed the increased loneliness risk associated with the absence of a spouse was stronger for men than for women [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Engagement in diverse social activities in later life has been reported to provide opportunities for older adults to exchange similar interests, share life experiences, and facilitate social connections, which may alleviate their loneliness [ 40 , 41 ]. Our findings support previous literature reporting the beneficial effect of social activity on late-life loneliness in both men and women [ 15 , 41 ]. Being married was associated with a lower likelihood of loneliness, but only among men, which is consistent with a Japanese study that showed the increased loneliness risk associated with the absence of a spouse was stronger for men than for women [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…Engagement in various community activities can reduce loneliness in older adults by providing human contact and intimacy [ 8 , 9 , 15 ]. The gerontological literature suggests that social networks and social connections can be important for psychological well-being in later life [ 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, we believe our estimate of costs may still be conservative. Loneliness, for example, can be associated with substantial economic costs, due to the increased risk of both physical and mental health problems [ 46 ]. Even though we identified high levels of loneliness in carers, we are not able to put a monetary value on these outcomes, nor can we assume that quality of life captures the impacts of loneliness, or even the stigma that may be associated with caring.…”
Section: Discussionmentioning
confidence: 99%